Utilising computerised tools and IT in new product development to constitute firms' financial performance and the impact of R&D intensity - Tanyanuparb Anantana (2018)
Copyright © 2015 Inderscience Enterprises Ltd. By using New Product Development Scorecard (NPDSC) as a data collecting tool, field surveys were conducted for 396 participating firms in 14 Japanese manufacturing industries. According to the results of the analyses, two elements of 'development strategy and organisation' and 'development production technology' are identified as enabling factors for the complement of utilising tools and IT in NPD. It is also suggested that in order to make a positive impact on financial performance, tools and IT should have to be incorporated with these enabling factors. In addition, it is found that level of utilisation capability of tools and IT is significantly higher in high R & D intensity groups compared to the low ones. And the level of R & D intensity affects the implementation methods of tools and IT for NPD and the contribution to financial performance, as well. Consequently, useful managerial implications are provided in this work.